2005
DOI: 10.1081/css-200042964
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Alfalfa Production on Coastal Plain Soils of the United States

Abstract: Alfalfa (Medicago sativa L.) is rarely grown on the Coastal Plain of southern United States. Production problems include infertile acid soils, inadequate pest control, and high humidity with frequent rainfall events that preclude adequate alfalfa hay drying conditions in spring. Research to overcome soil fertility problems included evaluation of nitrogen (N) rates over alfalfa row spacings and limestone and boron rates in split plot studies; phosphorus (P) rates using a randomized complete block design on eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Forage mass increased by 1,944 lb acre −1 to the 3‐yr mean for every 10‐inch increase in depth of a phytotoxic level of Al. With medium to high P levels present at our test site prior to fertilizer treatment application, our results validate those of Haby and Leonard (2005) in that other factors besides surface (<6 inches) nutrient availability contributed to stand decline and reduced FM in 2019. Though Al phytotoxicity was not measured in our study, highly weathered acid soils are prone to subsoil Al toxicity, even when surface pH is optimal; this was likely to have been a cause of diminished FM and PER in this field trial.…”
Section: Forage Mass and Persistencesupporting
confidence: 86%
See 3 more Smart Citations
“…Forage mass increased by 1,944 lb acre −1 to the 3‐yr mean for every 10‐inch increase in depth of a phytotoxic level of Al. With medium to high P levels present at our test site prior to fertilizer treatment application, our results validate those of Haby and Leonard (2005) in that other factors besides surface (<6 inches) nutrient availability contributed to stand decline and reduced FM in 2019. Though Al phytotoxicity was not measured in our study, highly weathered acid soils are prone to subsoil Al toxicity, even when surface pH is optimal; this was likely to have been a cause of diminished FM and PER in this field trial.…”
Section: Forage Mass and Persistencesupporting
confidence: 86%
“…Establishment year alfalfa FM in lighter Coastal Plain soils has shown varying responses to applied N, P, and K. Applied N significantly increased alfalfa FM for specific harvests conducted in east Texas. In Haby and Leonard's (2005) study, no significant yield differences were observed when N was applied at rates greater than 25 lb N acre −1 per harvest. In our field trial, N was applied at rates of 140 lb N acre −1 yr –1 for Treatments 1 and 3, and 280 lb N acre −1 yr –1 for Treatment 2.…”
Section: Forage Mass and Persistencementioning
confidence: 84%
See 2 more Smart Citations
“…Field-scale demonstrations have shown a considerable increase in alfalfa forage yields (3.9 Mg ha -1 or 159%) with B application. The sustainable economic production is possible under rainfed conditions on selected, limed Coastal Plain soils of US with improved methods of site selection, adequate fertility and management guidelines (Haby & Leonard, 2000.…”
Section: Alfalfamentioning
confidence: 99%